Optimization to detect TP53 mutations in circulating cell-free tumor DNA from patients with serous epithelial ovarian cancer - Yu Ran Park; Yong-Man Kim; Shin Wha Lee; Ha Young Lee; Gun Eui Lee; Jong-Eun Lee; Young-Tak Kim (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveCirculating cell-free tumor DNA (cfDNA) is the DNA released by apoptotic and necrotic cells of the primary tumor into the blood during the period of tumor development. The cfDNA reflects the genetic and epigenetic alterations of the original tumor. TP53 mutations are a defining feature of high-grade serous ovarian carcinoma. We optimized the methods for detecting TP53 mutations in cfDNA from blood samples. We confirmed the correlation of TP53 mutation in primary ovarian cancer tissue and it in cfDNA using digital polymerase chain reaction (dPCR).MethodsWe found 12 frequent mutation sites in TP53 using The Cancer Genome Atlas and Catalogue of Somatic Mutations in Cancer data and manufactured 12 primers. The mutations in tissues were evaluated in fresh-frozen tissue (FFT) and formalin-fixed paraffin-embedded tissue (FFPET). We performed a prospective analysis of serial plasma samples collected from 4 patients before debulking surgery. We extracted cfDNA and calculated its concentration in blood. dPCR was used to analyze TP53 mutations in cfDNA, and we compared TP53 mutations in ovarian cancer tissue with those in cfDNA.ResultsTen primers out of 12 detected the presence of TP53 mutations in FFT, FFPET, and cfDNA. In FFT and FFPET tissue, there were no significant differences. The average cfDNA concentration was 2.12±0.59 ng/mL. We also confirmed that mutations of cfDNA and those of FFT were all in R282W site.ConclusionThis study developed detection methods for TP53 mutations in cfDNA in ovarian cancer patients using dPCR. The results demonstrated that there are the same TP53 mutations in both ovarian cancer tissue and cfDNA.